Efficient Specification of Interneurons from Human Pluripotent Stem Cells by Dorsoventral and Rostrocaudal Modulation. (17th June 2014) - Kim, Tae-Gon; Yao, Ruiqin; Monnell, Travis; Cho, Jun-Hyeong; Vasudevan, Anju; Koh, Alice; Peeyush, Kumar T.; Moon, Minho; Datta, Debkanya; Bolshakov, Vadim Y.; Kim, Kwang-Soo; Chung, Sangmi
Abstract : GABAergic interneurons regulate cortical neural networks by providing inhibitory inputs, and their malfunction, resulting in failure to intricately regulate neural circuit balance, is implicated in brain diseases such as Schizophrenia, Autism, and Epilepsy. During early development, GABAergic interneuron progenitors arise from the ventral telencephalic area such as medial ganglionic eminence (MGE) and caudal ganglionic eminence (CGE) by the actions of secreted signaling molecules from nearby organizers, and migrate to their target sites where they form local synaptic connections. In this study, using combinatorial and temporal modulation of developmentally relevant dorsoventral and rostrocaudal signaling pathways (SHH, Wnt, and FGF8), we efficiently generated MGE cells from multiple human pluripotent stem cells. Most importantly, modulation of FGF8/FGF19 signaling efficiently directed MGE versus CGE differentiation. Human MGE cells spontaneously differentiated into Lhx6-expressing GABAergic interneurons and showed migratory properties. These human MGE-derived neurons generated GABA, fired action potentials, and displayed robust GABAergic postsynaptic activity. Transplantation into rodent brains results in well-contained neural grafts enriched with GABAergic interneurons that migrate in the host and mature to express somatostatin or parvalbumin. Thus, we propose that signaling modulation recapitulating normal developmental patterns efficiently generate human GABAergic interneurons. This strategy represents a novel tool in regenerative medicine, developmental studies, disease modeling, bioassay, and drug screening. Stem Cells   2014;32:1789–1804